Antimicrobial activities of Aloe vera leaf and clove extracts, their comparison with commercial antibiotics and molecular analysis of genes involved with multidrug resistance in bacteria - Afrin, Nusrat (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.